2011
DOI: 10.1007/s00531-010-0629-8
|View full text |Cite
|
Sign up to set email alerts
|

The tectonic significance of K/Ar illite fine-fraction ages from the San Luis Formation (Eastern Sierras Pampeanas, Argentina)

Abstract: The Sierra de San Luis forms the southern tip of the Eastern Sierras Pampeanas in central Argentina. Two narrow belts of low-grade phyllites and quartz arenites, i.e. the San Luis Formation, have accommodated part of the strain-related differential exhumation of the medium-to high-grade metamorphic domains that constitute to the basement complex of the sierra. Eleven phyllite samples were subjected to the K/Ar fine-fraction dating technique. Results are interpreted in relation to the Kübler index of the illite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…This time span matches with regional tectonic processes such as the development of the Paganzo Basin (Limarino and Spalletti, 2006;Gulbranson et al, 2010) and the San Rafael Orogeny (Ramos, 1988;Kleiman and Japas, 2009;Geuna et al, 2010;Japas et al, 2013). Active deformation during basin development was accompanied by exhumation of the study area, as indicated by K-Ar fine fraction data from Wemmer et al (2011) and thermochronological data presented here (Figs. 7, 10).…”
Section: Implications For the Evolution Of The Sierra De San Luissupporting
confidence: 83%
See 2 more Smart Citations
“…This time span matches with regional tectonic processes such as the development of the Paganzo Basin (Limarino and Spalletti, 2006;Gulbranson et al, 2010) and the San Rafael Orogeny (Ramos, 1988;Kleiman and Japas, 2009;Geuna et al, 2010;Japas et al, 2013). Active deformation during basin development was accompanied by exhumation of the study area, as indicated by K-Ar fine fraction data from Wemmer et al (2011) and thermochronological data presented here (Figs. 7, 10).…”
Section: Implications For the Evolution Of The Sierra De San Luissupporting
confidence: 83%
“…14), yielding Devonian ages (380-350 Ma; Sims et al, 1998;Steenken et al, 2008) and Carbonifeous K-Ar fine fraction ages (345-299 Ma; Wemmer et al, 2011). The latter ages were taken from the San Luis Formation, represented by two belts of low-grade phyllites and quartz arenites, several kilometres to the north of the study area.…”
Section: 2 Timing Of Faulting Constrained By K-ar Agesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine-fraction K-Ar dating has been used in a number of studies producing reliable age constraints on low-grade metamorphism (e.g. Wemmer et al 2011;Koehl et al 2018). That technique was therefore also used in this study.…”
Section: Sample Description and Methodsmentioning
confidence: 99%
“…On the other hand, the Tres Árboles ultramylonites have yielded much younger 40 Ar-39 Ar ages of 343 ± 5 and 341 ± 5 Ma (Whitmeyer 2008), respectively, although these were interpreted as regional cooling ages and can only be regarded as minimum estimates for the cessation of fault movement. Wemmer et al (2011) obtained K-Ar ages of 334-291 Ma for fine-grained illite from phyllites associated with shear zones in Sierra de San Luis. They considered that the ages older than 320 Ma correspond to a phase of compressional tectonism linked with the Toco orogeny that is recognized in northern Chile and southern Bolivia.…”
Section: Comparison With the Achala Batholith And Geodynamic Implicatmentioning
confidence: 99%